Find the value of such that the above equation is true.
Details and Assumptions
The subscript represents number base.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We need to find t h e n u m b e r b a s e i n w h i c h b a s e 3 1 i s i n . To do this, use the method of how to express numbers in certain number base:
3 1 x = 3 x + 1
Now substitute this into 1 6 2 and 6 5 (again, to express numbers in number bases):
1 ( 3 x + 1 ) 2 + 6 ( 3 x + 1 ) + 2 ( 3 x + 1 ) 0 = 3 ( 6 ( 3 x + 1 ) + 5 ( 3 x + 1 ) 0 ) ⟶
1 ( 3 x + 1 ) 2 + 6 ( 3 x + 1 ) + 2 = 3 ( 6 ( 3 x + 1 ) + 5 ) ⟶
9 x 2 − 3 0 x − 2 4 = 0
Solving this quadratic equation gives x = 4 and x = 3 − 2 . Of course number bases can't be negative so x = 4
Plug in 4 and the answer equation is true.